Mekanisme Valensi Morfologis pada Verba Bahasa Indonesia - Herpindo, Herpindo; Wulandari, Sri; Ristiyani, Ristiyani; Nikmatullah, Miftahula Rizqin (Jurnal Bahasa dan Sastra, 2024)
As a language with agglutinative morphology type, Indonesian has not shown serious firmness in various morphological cases, especially valency mechanism caused by morphology + verb process. To deeply dissect the valency mechanism, especially inflected verbs in Indonesian, a qualitative method with descriptive type is used with agih (distributional) method and direct element sharing technique to analyze the data. The results of this study show the existence of valency mechanisms in the form of inflected verbs in Indonesian, namely (1) valency increase in the causative morphological structure with {meN-kan} marker, (2) valency increase in the benefactive applicative structure with {di-kan} marker, (3) valency increase in the locative applicative structure with {meN-i} marker, (4) valency decrease in the ergative sentence structure with morphological cases {ter-}, {ke-an}, and {∅}. This study shows various valency mechanisms that are dominant in inflected verbs even though in some cases they appear in ergative forms that do not have markers.